The Pathogenic Potential of Campylobacter concisus Strains Associated with Chronic Intestinal Diseases - Kaakoush, Nadeem O.; Deshpande, Nandan P.; Wilkins, Marc R.; Tan, Chew Gee; Burgos-Portugal, Jose A.; Raftery, Mark J.; Day, Andrew S.; Lemberg, Daniel A.; Mitchell, Hazel (PLOS ONE, 2011)
Campylobacter concisus has garnered increasing attention due to its association with intestinal disease, thus, the pathogenic potential of strains isolated from different intestinal diseases was investigated. A method to isolate C. concisus was developed and the ability of eight strains from chronic and acute intestinal diseases to adhere to and invade intestinal epithelial cells was determined. Features associated with bacterial invasion were investigated using comparative genomic analyses and the effect of C. concisus on host protein expression was examined using proteomics. Our isolation method from intestinal biopsies resulted in the isolation of three C. concisus strains from children with Crohn's disease or chronic gastroenteritis. Four C. concisus strains from patients with chronic intestinal diseases can attach to and invade host cells using mechanisms such as chemoattraction to mucin, aggregation, flagellum-mediated attachment, “membrane ruffling”, cell penetration and damage. C. concisus strains isolated from patients with chronic intestinal diseases have significantly higher invasive potential than those from acute intestinal diseases. Investigation of the cause of this increased pathogenic potential revealed a plasmid to be responsible. 78 and 47 proteins were upregulated and downregulated in cells infected with C. concisus, respectively. Functional analysis of these proteins showed that C. concisus infection regulated processes related to interleukin-12 production, proteasome activation and NF-κB activation. Infection with all eight C. concisus strains resulted in host cells producing high levels of interleukin-12, however, only strains capable of invading host cells resulted in interferon-γ production as confirmed by ELISA. These findings considerably support the emergence of C. concisus as an intestinal pathogen, but more significantly, provide novel insights into the host immune response and an explanation for the heterogeneity observed in the outcome of C. concisus infection. Moreover, response to infection with invasive strains has substantial similarities to that observed in the inflamed mucosa of Crohn's disease patients.